Students' view on using web-based resources in learning: Qualitative study / Peridah Bahari and Salina Hamed - Bahari, Peridah; Hamed, Salina (Universiti Teknologi MARA, Pulau Pinang & Pusat Penerbitan Universiti (UPENA), 2008)
The widespread acceptance of Web Technology in our tertiary institutions has brought about changes in the style, quantity, and variety of resources that are made available to students. A new learning environment is available for students. However, there are still questions regarding the readiness of students in using the abundant resources made available to them on the Web. This study examines students' readiness in using web-based resources. Variables that were looked into are the level of technology usage, perspective on technology, motivation and attitude, learning styles, and expected support. Thirteen interviews were conducted randomly on diploma and degree engineering students (electrical, mechanical, and civil). Results obtained showed that students take the term web -based resources to be synonymous with the Internet, rating themselves as novices in computer usage, and commented that web-based resources could provide them with the latest and useful extra information. Responses given showed that students are mentally ready but not technically ready.